Spatial and temporal heterogeneity of ventilator-associated lung injury after surfactant depletion - Otto, Cynthia M; Markstaller, Klaus; Kajikawa, Osamu; Karmrodt, Jens; Syring, Rebecca S; Pfeiffer, Birgit; Good, Virginia P; Frevert, Charles W; Baumgardner, James E (Journal of applied physiology (1985), 2008)
1 Department of Anesthesiology and Critical Care, University of Pennsylvania, Philadelphia, Pennsylvania; 2 Oscillogy, Folsom, Pennsylvania; 3 Department of Clinical Studies-Philadelphia, School of Veterinary Medicine, and 4 Center for Sleep and Respiratory Neurobiology, University of Pennsylvania, Philadelphia, Pennsylvania; 5 Department of Anesthesiology, Johannes Gutenberg-University, Mainz, Germany; 6 Division of Pulmonary and Critical Care Medicine, Department of Medicine, University of Washington, Seattle Washington; and 7 Department of Anesthesiology and Intensive Care Medicine, Otto-von-Guericke-University, Magdeburg, Germany Submitted 11 October 2007 ; accepted in final form 3 March 2008 Volutrauma and atelectrauma have been proposed as mechanisms of ventilator-associated lung injury, but few studies have compared their relative importance in mediating lung injury. The objective of our study was to compare the injury produced by stretch (volutrauma) vs. cyclical recruitment (atelectrauma) after surfactant depletion. In saline-lavaged rabbits, we used high tidal volume, low respiratory rate, and low positive end-expiratory pressure to produce stretch injury in nondependent lung regions and cyclical recruitment in dependent lung regions. Tidal changes in shunt fraction were assessed by measuring arterial P O 2 oscillations. After ventilating for times ranging from 0 to 6 h, lungs were excised, sectioned gravitationally, and assessed for regional injury by evaluation of edema formation, chemokine expression, upregulation of inflammatory enzyme activity, and alveolar neutrophil accumulation. Edema formation, lung tissue interleukin-8 expression, and alveolar neutrophil accumulation progressed more rapidly in dependent lung regions, whereas macrophage chemotactic protein-1 expression progressed more rapidly in nondependent lung regions. Temporal and regional heterogeneity of lung injury were substantial. In this surfactant depletion model of acute lung injury, cyclical recruitment produced more injury than stretch. acute lung injury; chemokines; inflammation Address for reprint requests and other correspondence: J. E. Baumgardner, Oscillogy, LLC, 131 Milmont Ave., Folsom, PA 19033 (e-mail: jbaumgardneratoscillogy.com )